Indoor Air Monitoring and Filtration Using Arduino-Based Plasma Technology - Adi Sofyan; Dendy Kurniawan (University of Science and Computer Technology, 2023)
In public service offices in the government, special areas or rooms are provided for smoking. At the Kendal District Court Class 1B the smoking room or smoking area still uses air ventilation and fans to neutralize cigarette smoke. As a result, the smoke that is exposed to the fan in the smoking room spreads out and disturbs the health of the surrounding community or disrupts the activities of employees at the Kendal Class 1B District Court. In this case, the Kendal Class 1B District Court, especially this smoking area, needs to be handled, namely making a device that can filter cigarette smoke and monitor the condition or level of air quality in the room so that cigarette smoke does not spread outside the room and harm your health. To help the filtration system in smoking rooms, there needs to be an automatic system that is able to work when cigarette smoke in the room is at a certain level. The sensors used to detect levels of CO ( carbon monoxidant), CO2 (carbon dioxidant) in cigarette smoke are MQ-7 and MQ-135. The way this tool works, if cigarette smoke in the room reaches the threshold level of gas in the room, the fan will suck it into the filtration room, after which it will be exhaled back into the smoking room and will notify the condition of the room on the LCD monitor display.